Pharmaceutical guidance and the impact on medication adherence in patients with amyloidosis - Aline EVANGELISTA; Mariana Cappelletti GALANTE; Sonia Lucena CIPRIANO; Fabio FERNANDES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objectives: To identify medication adherence in patients with Cardiac Amyloidosis (CA) before and after pharmaceutical guidance and investigate its association with quality of life. Methods: This is a before-and-after, single-arm, non-randomized study. The selection was among patients with transthyretin (TTR) cardiac amyloidosis included in research protocols of the Instituto do Coração do Complexo do Hospital das Clínicas da Universidade de São Paulo (InCor HCFMUSP). Five pharmaceutical visits were performed, the first in person and the others by telehealth. The Kansas City Cardiomyopathy Questionnaire (KCCQ) and Brief Medication Questionnaire (BMQ) quality of life questionnaires were used. Medication adherence was identified and classified into four categories: adherent, probable adherent, probable low adherent, and low adherent. To estimate the association between medication adherence and quality of life, analysis was performed using ANOVA and unpaired t-test. Results: 11 participants agreed to participate in all study visits. Mean age was 74.2 years (SD= 8.4), 95.2% were male, and 47.6% had completed college education. The mean number of medications in use was 8 (dp= 2.9). 54.5% of participants were classified as adherent. The association between medication adherence and quality of life was significant for the Total Symptom Score and Clinical Summary domains. There was no significance in the correlations between the number of medications and KCCQ. Conclusions: Pharmacotherapy follow-up mediated by telehealth for patients with Cardiac Amyloidosis can improve in at least one domain of KCCQ.